Vegetation phenology as a key driver for fire occurrence in the UK and comparable humid temperate regions - Tadas Nikonovas (International Journal of Wildland Fire, 2024)
BackgroundFire activity in the UK and comparable regions of northwest Europe is generally out of phase with peak fire weather conditions.AimsHere, we assess the potential effect of phenology on fire occurrence patterns for the UK.MethodsWe examined fire occurrence and vegetation phenology in the UK for 2012–2023, mapped onto the main fire-affected vegetation cover types within distinct precipitation regions, allowing the fire occurrence for fuels in different phenological phases to be explored across distinct ‘fuel’ types and regions.Key resultsThe UK’s fire regime is characterised by burning in semi-natural grasslands and evergreen dwarf shrub ecosystems in early spring when vegetation is still dormant. During the high-greenness phase in late spring and summer, fire activity is reduced by a factor of 5–6 despite typically elevated fire weather conditions within that period.Conclusions and implicationsSemi-natural vegetation in the UK is very resistant to burning during the high-greenness phase. However, this ‘fire barrier’ is diminished during severe drought episodes, which are predicted to become more extreme in the coming decades. Incorporating phenology information into models therefore has great potential for improving future fire danger and behaviour predictions in the UK and comparable humid temperate regions.